2020
DOI: 10.28933/ijoar-2020-06-1305
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless Tobacco dependence and cessation measures in India

Abstract: Review Article IJOAR (2020) 3:68 Smokeless Tobacco dependence and cessation measures in India India being the largest smokeless tobacco (SLT) producer and consumer in the South East Asia Region (SEAR) entitled with a range of products. SLT consumption is very common because it is associated with socioeconomic and cultural perspectives in the India. After the implementation of the first treaty of the World Health Organization Framework Convention on Tobacco Control (WHO-FCTC), public health standards were reaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This gap in support and intervention was also evident in our study, as individuals who had successfully quit for a short period ultimately returned to using tobacco due to the lack of adequate support. This finding is consistent with the results of our study [ 47 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This gap in support and intervention was also evident in our study, as individuals who had successfully quit for a short period ultimately returned to using tobacco due to the lack of adequate support. This finding is consistent with the results of our study [ 47 ].…”
Section: Discussionsupporting
confidence: 94%
“…It is noteworthy that most of these individuals achieved cessation through self-treatment at home, as access to standard quit programs was limited, particularly for low-income participants. A similar study conducted in India also reported a lack of access to standard treatment programs among low-income individuals [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the COTPA act and MPOWER strategies, tobacco use has declined significantly. However, tobacco consumption remains a burning issue due to the poor implementation and dissemination of law and policy [ 50 ].…”
Section: Discussionmentioning
confidence: 99%